(untitled) (Annals of Medical Research, 2025)
Aim: Patients receiving HD are more prone to accidental falls than elderly individuals not undergoing HD, leading to higher morbidity and mortality in this group. In this study, we hypothesized that senior HD patients with a history of falls may have impaired ankle kinesthetic position sense. Materials and Methods: This study included 63 hemodialysis patients aged 65 and older. Baseline Timed Up and Go (TUG) test durations and ankle joint inclinometric deviation measurements were assessed in all participants, who were then monitored for fall events over a 12-month period. Patients who experienced one or more falls were classified as the faller group, while the rest were categorized as the non-faller group. Demographic data, laboratory values, TUG test durations, and ankle joint inclinometric deviations were compared between the two groups. Results: Among the 63 patients, 25 (39.7%) were classified as fallers. The mean inclinometric deviation for the entire study population was 4.1±1.9 degrees. Notably, patients in the faller group had a significantly higher deviation (5.5±1.9) compared to those in the non-faller group (3.1±1.2, p=0.000). Age, serum albumin levels, TUG test duration, inclinometric deviation of patients have been included in the logistic regression analysis. Of these parameters, only inclinometric deviation (OR=2.627, p=0.003) was determined as an independent predictor of falls. Conclusion: Falls are prevalent among elderly hemodialysis patients, and impairment of ankle kinesthetic position sense is evident in those who have experienced falls.